Rats to Palm Trees: Baiting the Canopy During the Palmyra Atoll Rat Eradication Project - Wegmann, Alexander; Stansbury, Rory; Alifano, Aurora; Oberg, Erik; Pott, Madeleine; McClelland, Pete; Howald, Gregg (Proceedings of the Vertebrate Pest Conference, 2014)
Rodent eradication campaigns on tropical islands face challenges not experienced in temperate climates, such as competition for bait by land crabs and extensive use of the forest canopy by rats. In 2011, black rats were successfully eradicated from Palmyra Atoll with a campaign built on lessons learned from a prior, unsuccessful ground-based eradiation attempt. The 2011 eradication team, at considerable cost and effort, ensured that bait (brodifacoum, 0.0025%) was placed in every potential rat territory, including the atoll’s coconut palm canopy. Coconut palm is the dominant canopy tree at Palmyra, covering 45% of the 235 ha land area. Bait applied to palm crowns is not available to land crabs and persists longer than bait placed on the ground. Rats were frequently observed traveling to and from the crowns of palms overhanging the water, yet this important habitat could not be treated by aerial broadcast (the primary bait application method) as this would place bait into the marine environment. To deliver bait to overhanging palms lining Palmyra’s shoreline, we developed a “bola” canopy bait (BCB) ‒ two cotton-gauze sacks connected by 20 cm of twine, each containing 12.5g of bait. A manufacturing system was created to produce the quantities of BCBs needed to treat Palmyra’s overhanging palm habitat. BCBs were slung by hand or with a sling-shot, or dropped into palm crowns by a team member suspended beneath a helicopter. Handheld GPS units were used to record the location of each palm crown treated with a BCB so that the bait application could be tracked. We believe that the successful outcome of the 2011 eradication was due, in part, to the comprehensive treatment of Palmyra’s palm canopy.